Peptic ulcer bleeding: accessory risk factors and interactions with non-steroidal anti-inflammatory drugs. Issue 1 (1st January 2000) - Weil, J; Langman, M J S; Wainwright, P; Lawson, D H; Rawlins, M; Logan, R F A; Brown, T P; Vessey, M P; Murphy, M; Colin-Jones, D G
Abstract : AIMS: To determine risk factors for peptic ulcer bleeding other than non-steroidal anti-inflammatory drugs (NSAIDs) . Methods—Data on possible antecedent risk factors obtained in a large case control study of 1121 patients admitted to hospitals in Glasgow, Newcastle, Nottingham, Oxford, and Portsmouth with bleeding peptic ulcers were compared with the same information obtained in 989 population controls. Data were analysed by logistic regression with the calculation of odds ratios (OR) and 95% confidence intervals (CI). RESULTS: From a logistic regression model, oral anticoagulants (OR 7.8; 95% CI 2.8–21.5), previous peptic ulcer (3.8; 2.6–4.9), treatment for heart failure (5.9; 2.3–13.1), oral corticosteroid use (2.7; 1.3–4.5), treatment for diabetes (3.1; 1.2–4.3), and current smoking (1.6; 1.2–2.0) were all independent risk factors. No association was found with use of calcium channel antagonists. Odds ratios for concomitant NSAID usage were multiplicative with the exception of current smoking. CONCLUSIONS: Some 45% of admissions for peptic ulcer bleeding in England and Wales in those aged 60 or more are calculated to be attributable to, or associated with, these accessory risk factors, which, together with those associated with aspirin or other NSAID use will account for over 80% of predisposing factors to ulcer bleeding.